Marriage Dispensation and Family Resilience: A Case Study of the Bener Meriah Shariah Court, Aceh Province - Darmawan Darmawan; Asmaul Husna; Mirza Rahmatillah; Helmi Imran (AHKAM : Jurnal Ilmu Syariah, 2022)
The regulation on marriage dispensation has encouraged the increase in early marriage in various regions in Indonesia, including in Bener Meriah, Aceh.  Early  marriage  has  a  negative  impact  on  family  resilience  as  it  raises problems leading to divorce. This is a normative legal study with a case study approach. Data collection was carried out employing a document study, namely Sharia Court Decisions and related literature. This study concludes a significant relationship  between  marriage  dispensation,  high  underage  marriages,  and weak family resilience. In granting marriage dispensation, the Sharia Court judges consider legal and extra-legal grounds. The dispensation stipulation has met  the  legal  requirement,  although  the  legal  reasonings  are  unconvincing. Furthermore, early marriage has an impact on increasing divorce rates due to issues such as psychological problems and reproductive readiness, as well as adverse effects caused by divorce. Therefore, concrete and strategic steps are needed  with  the  involvement  of  various  groups,  including  the  government, ulama, and traditional leaders, who are able to promote family resilience in society.Keywords: marriage dispensation; underage marriage; family resilience; sharia court AbstrakKebijakan dispensasi nikah telah mendorong peningkatan pernikahan dini  di  berbagai  daerah  di  Indonesia,  termasuk  di  Bener  Meriah,  Aceh. Pernikahan  dini  berdampak  negatif  terhadap  ketahanan  keluarga  karena menimbulkan masalah yang berujung pada perceraian. Penelitian ini merupakan penelitian  hukum  normatif  dengan  pendekatan  studi  kasus.  Pengumpulan data  dilakukan  dengan  studi  dokumen  yaitu  Putusan  Mahkamah  Syar’iyah dan literatur terkait. Penelitian ini menyimpulkan bahwa terdapat hubungan yang signifikan antara dispensasi perkawinan, tingginya angka perkawinan di bawah umur dan lemahnya ketahanan keluarga. Dalam pemberian dispensasi nikah,  hakim  Mahkamah  Syar’iyah  mempertimbangkan  alasan  hukum  dan alasan di luar hukum. Ketentuan dispensasi tersebut telah memenuhi syarat hukum,  meskipun  pertimbangan  hukumnya  tampak  memaksakan.  Lebih lanjut,  pernikahan  dini  berdampak  pada  meningkatnya  angka  perceraian karena masalah-masalah seperti masalah psikologis dan kesiapan reproduksi, serta dampak buruk akibat perceraian. Oleh karena itu, diperlukan langkah- langkah  konkrit  dan  strategis  dengan  melibatkan  berbagai  pihak,  termasuk pemerintah,  ulama,  dan  tokoh  adat,  yang  mampu  mendorong  ketahanan keluarga dalam masyarakat.Kata Kunci: dispensasi  pernikahan;  pernikahan  dini;  ketahanan  keluarga; Mahkamah Syar’iyah